Protocol for a realist evaluation of Recovery College dementia courses: understanding coproduction through ethnography - Birt, L; West, J; Poland, F; Wong, G; Handley, M; Litherland, R; Hackmann, C; Moniz-Cook, E; Wolverson, E; teague, B; Mills, R; Sams, K; et al. (BMJ Publishing Group, 2023)
Introduction: Support following a dementia diagnosis in the UK is variable. Attending a Recovery College course with and for people with dementia, their supporters and healthcare professionals (staff), may enable people to explore and enact ways to live well with dementia. Recovery Colleges are established within mental health services worldwide, offering peer-supported short courses coproduced in partnership between staff and people with lived experience of mental illness. The concept of recovery is challenging in dementia narratives, with little evidence of how the Recovery College model could work as a method of postdiagnostic dementia support. Methods and analysis: Using a realist evaluation approach, this research will examine and define what works, for whom, in what circumstances and why, in Recovery College dementia courses. The ethnographic study will recruit five case studies from National Health Service Mental Health Trusts across England. Sampling will seek diversity in new or long-standing courses, delivery methods and demographics of population served. Participant observations will examine course coproduction. Interviews will be undertaken with people with dementia, family and friend supporters and staff involved in coproducing and commissioning the courses, as well as people attending. Documentary materials will be reviewed. Analysis will use a realist logic of analysis to develop a programme theory containing causal explanations for outcomes, in the form of context-mechanism-outcome-configurations, at play in each case. Ethics and dissemination: The study received approval from Coventry & Warwickshire Research Ethics Committee (22/WM/0215). Ethical concerns include not privileging any voice, consent for embedded observational fieldwork with people who may experience fluctuating mental capacity and balancing researcher ‘embedded participant’ roles in publicly accessible learning events. Drawing on the realist programme theory, two stakeholder groups, one people living with dementia and one staff will work with researchers to coproduce resources to support coproducing Recovery College dementia courses aligned with postdiagnostic services.